Teaching of English in India : Issues and Concerns - Kapur, Dr. Kirti (Voices of Teachers and Teacher Educators, 2017)
Teaching English as a second language requires consideration of various aspects of language learning. First and foremost, we need to appreciate the fact that India is a multilingual country and English does not stand alone, it needs to find a place along with other Indian Languages. Approaches such as the communicative approach, the natural approach and the whole language approach, which have recently gained momentum in India, all lay stress on providing meaningful, communicational chunks of language to the learners. Language is best acquired through meaningful contexts and languages are learnt implicitly and not explicitly. Teachers too need to develop their own reading, writing, speaking and listening skills, so that they can help learners improve their skills by providing appropriate opportunities and doing activities with the learners and be able to use language in an integrated manner and enable the learners to develop their creative and critical faculties. This in turn will facilitate them to study and understand other subjects better. After all, language cuts across all the subjects included in the curriculum.